Acute myeloid leukaemia presenting with diabetes insipidus. Issue 6 (11th June 2019) - Bardin, Michele; Ritchie, David; McLachlan, Robert; Yates, Christopher J.
Abstract: A 41‐year‐old man was diagnosed with hypogonadotropic hypogonadism managed with gonadotropins after routine fertility review. Eight months later he presented with new polydipsia and polyuria, lethargy and easy bruising. A full blood count showed 28% circulating blasts. A bone marrow biopsy confirmed a diagnosis of acute myeloid leukaemia with inv(3)(q21.3q26.2) with additional monosomy 7. Central diabetes insipidus (DI) was diagnosed following a water deprivation test. Pituitary magnetic resonance imaging showed a slightly thickened pituitary stalk, stable Rathke's cyst, and new absence of the pituitary bright spot. The patient was commenced on desmopressin and induction chemotherapy, subsequently requiring a bone marrow transplant. Bone marrow examination at 100 days post‐transplant revealed cytogenetic remission. All symptoms of DI resolved and magnetic resonance imaging showed return of the posterior bright spot and a pituitary stalk of normal thickness. Biochemical hypogonadotropic hypogonadism persisted but was uninterpretable in the context of systemic illness and recent chemotherapy. DI is a rare complication of haematological malignancies, and the prevalence and pathophysiology of DI in this context are poorly understood. Pathogenic mechanisms proposed include leukaemic infiltration of the pituitary, interference with antidiuretic hormone synthesis, and abnormal thrombopoiesis influencing hormone levels. Particular cytogenetic abnormalities such as inv(3)(q21.3q26.2) and monosomy 7 appear to be more commonly associated with DI and also appear to confer worse outcomes. Aetiologies in the literature remain elusive but as DI is a recognised association of haematological malignancies it should be considered in a patient presenting with polydipsia and polyuria.